Argamassas para dessalinização de alvenaria mista de edifício histórico de Belém - LOUREIRO, Alexandre Máximo Silva (Universidade Federal do Pará, 2013)
In the historical monuments of Belém structural masonry, along with the foundations and pillars, are responsible for supporting the building (VASCONCELLOS, 1979). These masonry are made of stone and solid bricks with lime mortar setting and can present various pathologies among which stand out the action of salt efflorescence and moisture. These two agents cause detachment of layers, mortar spraying, the appearance of cracks in masonry, and whitish appearance (HENRIQUES, 1994; CHAROLA, 2000). The research has as main objective the identification, characterization and attenuation of salt efflorescence, through study of the masonry of the right transept of the Church of St. Alexandre, located in historic downtown of Belém- PA. For this, laboratory techniques were used in order to understand the favorable process conditions of salt efflorescence, the damage to the materials, the kinds of salts and which materials are effective for desalination. First was the mapping the masonry and mapping damage to verify the current situation and the most degraded areas. Was subsequently performed the physical, chemical and mineralogical characterization: 1) physical characterization by sieve analysis, trace analysis and analysis of the moisture content of the masonry, 2) chemical characterization through qualitative and quantitative testing of salts and 3) characterization mineralogy by X-ray diffraction. The X-ray diffraction was also used to evaluate the efficacy of four types of desalination mortars containing clay (bentonite and kaolin) and sand in different ratios. At the end of the study it was found that the suggested techniques for characterization and mapping of the masonry proved efficient and aided in the correct diagnosis of the existing problem. Moreover, the research showed which kinds of mortar are recommended to desalination of masonry damaged by salt efflorescence.